![\frac{3x - 1}{4} - \frac{4x - 1}{3} = 0 \frac{3x - 1}{4} - \frac{4x - 1}{3} = 0](https://tex.z-dn.net/?f=+%5Cfrac%7B3x+-+1%7D%7B4%7D++-++%5Cfrac%7B4x+-+1%7D%7B3%7D++%3D+0)
ajuda eu aweeee
Soluções para a tarefa
Respondido por
0
(3x - 1)/4 - (4x - 1)/3 = 0
Precisamos deixar as duas frações com o mesmo divisor, então:
(3x - 1)/4.(3/3) - (4x - 1)/3.(4/4) = 0
3.(3x - 1)/12 - 4.(4x - 1)/12 = 0
(9x - 3)/12 - (16x - 4)/12 = 0
(16x - 4)/12 = (9x - 3)/12
16x - 4 = 9x - 3
16x - 9x = 4 - 3
7x = 1
x = 1/7
Resposta: 1/7
Perguntas interessantes
Português,
10 meses atrás
Contabilidade,
10 meses atrás
Inglês,
10 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás